Nanomaterials Developed by Processing Iron Coordination Compounds for Biomedical Application. (25th March 2019) - Iacob, Mihail; Racles, Carmen; Dascalu, Mihaela; Tugui, Codrin; Lozan, Vasile; Cazacu, Maria
Abstract : The iron oxides, widespread in nature, are used in numerous applications in practice due to their well-known properties. These properties can be modified by size lowering at nanoscale. Some applications, such as biomedical, require a rigorous selection of nanoparticles by size, shape, and surface functionality. In other applications, such as catalysis or magnetism, the composition (generally mixed oxides) and morphology of the nanoparticles are of high importance. The preparation of iron oxide nanoparticles (IONPs) is a complex process whose control raises a number of issues. The first challenge is finding the optimal experimental conditions, which would lead to the preparation of monodisperse nanoparticles. Another issue is the selection or setting a reproducible and clean manufacturing process without a need of complex purification. Even though at the moment several methods for preparing IONPs are known, there are still concerns in the scientific world to further improve existing methods or create new protocols. Therefore, the establishment of optimal methods for preparing IONPs with predetermined structural, dimensional, and morphological characteristics is an important task of scientists. Most of the methods reported in literature for the preparation of IONPs use proper metal salts as precursors. Recently, the use of the organometallic and coordination compounds of iron as precursors for IONPs has emerged as an alternative for a better control of these. Here, achievements reported in the literature in this direction are reviewed and critically analysed in relation to the conventional method based on iron salts.